Exposure assessment of operators to pesticides in Kongou, a sub-watershed of Niger River valley. Issue 3 (4th March 2019) - Illyassou, Karimoun M.; Adamou, Rabani; Schiffers, Bruno
Abstract: The use of pesticides in horticultural sector in Niger has become an integral part of modern agriculture. Nevertheless, their inappropriate use can generate negative health effects to operators. A study was carried out among Kongou farmers in order to assess their potential dermal exposure (PDE). The UK-POEM model was used to quantify the PDE during mixing/loading and application according to the local practices. In order to determine which parts of the operator body are subject to most contamination during spraying and to validate the theoretical model used, a patch method was used with a tartrazine dye. The deposits of the tartrazine on patches were measured by colorimetry thanks to the absorbance value determined after their extraction in water and a calibration curve. A total of ten spraying trials (five trials with the hand-held sprayer and five others with the backpack sprayer) were performed by different producers at 0.5 and 1 m height for each trial. The survey shows that 92% of the farmers are illiterate and the most common active substances identified are organophosphate or pyrethroids insecticides. Seventy percent of operators do not use any personal protective equipment (PPE) during mixing/loading or spraying. The predictive systemic exposure levels vary from 0.0027 mg kg −1  bw per day to 0.7692 mg kg −1  bw per day for backpack sprayer and from 0.0261 mg kg −1  bw per day to 0.9788 mg kg −1  bw per day for hand-held sprayer, several times higher the Acceptable Operator Exposure Level (AOEL) for some actives substances. Theoretical modeling indicates more exposure of operator by a hand-held sprayer than a backpack sprayer. The patch method results show that the deposits of dye increase when the position of sprayer nozzle increases from 0.5 to 1 m for the two sprayers. All parts of the operator body are contaminated but lower body parts and chest are the most exposed. The patch method results also show that hand spraying contaminates operator more than backpack spraying, confirming the results of the theoretical model.